1977
DOI: 10.1172/jci108780
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Adaptation of Left Atrial Stretch Receptors in Dogs with Chronic Congestive Heart Failure

Abstract: A B S T R A C T Chronic congestive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(44 citation statements)
references
References 48 publications
4
40
0
Order By: Relevance
“…Another possibility is that the mechanoreceptors in patients with CHF are abnormal. Zucker et al 20 reported that atrial receptors were abnormal in the dog with induced heart failure. Carotid and aortic baroreceptor function could also be impaired in heart failure.21…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that the mechanoreceptors in patients with CHF are abnormal. Zucker et al 20 reported that atrial receptors were abnormal in the dog with induced heart failure. Carotid and aortic baroreceptor function could also be impaired in heart failure.21…”
Section: Discussionmentioning
confidence: 99%
“…We measured SNA, MAP, cardiac filling pressure (as either pulmonary artery pressure [PAP] or pulmonary capillary wedge pressure), and cardiac output responses during ventricular pacing at a cycle length of 400 ms under 3 conditions: pacing alone, pacing plus head-up tilt (20 o to 30 o ) to a level that returned cardiac filling pressure to prepacing baseline levels, and pacing plus phenylephrine infusion sufficient to return MAP to prepacing baseline levels. Pacing was sustained for 4 to 5 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…In a similar preparation of canine heart failure, Greenberg et al3 demonstrated decreased sensitivity of atrial type B receptors to volume loading. Zucker et al 4 showed that dogs with heart failure induced by aortocaval fistula had marked attenuation of the sensitivity of medulated left atrial type B receptors to any given change in left atrial pressure. The mechanism for this depressed sensitivity was thought to be due to a decreased left atrial compliance and structural alterations in the neural receptor endings with loss of their normally distinct end-arborizations.…”
Section: Methodsmentioning
confidence: 99%